Femmebook: Women, Facebook and the #NoMakeUpSelfie - Smith, Amber (Université d'Ottawa | University of Ottawa, 2015)
The purpose of this study was to critically examine how young women conform to and subvert our culture’s dominant gender norms and the role social networking sites, such as Facebook, play in this process. The study used a qualitative research approach and semi-structured interviews to collect data. The findings indicate that Facebook is an essential communication tool in the lives of young women that serves to reinforce and disseminate social and gender norms. The study found that gender norms are so deeply ingrained and normalized in our society that women conform to them, often without realizing they are doing so. The #NoMakeUpSelfie campaign provided a case study where women were unwittingly reinforcing existing—not entirely positive—gender norms which reinforced culturally held beliefs that a women’s femininity is her strongest and most valuable asset.